PERANCANGAN SISTEM PENGOLAHAN DATA SIMPAN PINJAM PADA KOPERASI PEGAWAI NEGERI ( KPN ) PENGADILAN AGAMA SIJUNJUNG DIDUKUNG DENGAN BAHASA PEMOGRAMAN VISUAL BASIC - Jamhur, Annisak Izzaty (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Finance is a main element in an institution and organization. In the implementation ofgood finance must be supported by a good financial information system. In the CivilServants Cooperative religion court Sijunjung implementing financial systems without theuse of a computerized process. The Civil Servants Cooperative of the religion courtSijunjung also experienced problems such as the calculation of the financial statementsthat were slow from the Treasurer section to the Leader and frequent miscalculation in thepreparation of financial statements. To deal with these problems a well integrated systemis needed. Data was collected by interview method, observation in the field and requestingthe required reports. By using this technique to obtain a financial cooperative database ofthe Civil Servants Cooperative Religion Court Sijunjung was obtained with several files /tables. The information system is expected designed to improve the efficiency andeffectiveness of the financial reporting and be able to deal with the problems encounteredKey Word : Cooperative